Stress and long-term potentiation - Shakesby, Alison (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2001)
Stress is a physiological reaction which the body copes with by a variety of mechanisms in order to restore homeostasis. Amongst these is an increase in plasma glucocorticoids, catecholamines and increases in brain neurotransmitters. Stress has been shown to have detrimental effects upon synaptic plasticity, blocking a form known as long-term potentiation (LTP) which is believed to be, in part, responsible for memory formation. The effect of stress on synaptic plasticity was assessed in anaesthetised rats. Electrodes were implanted into the CA1 region of the hippocampus and field excitatory postsynaptic potentials (EPSP) amplitudes were measured. The ability of rats to express LTP was assessed using a stimulation protocol of single high frequency stimulation (HFS) for induction. Rats were stressed by placement for 30 minutes upon a raised platform. The effect upon the ability to induce LTP was then investigated.
Keywords: Pharmacology and Therapeutics, Ph.D.; Ph.D. Trinity College Dublin